Interactions between 2 Mediterranean rodent species: Habitat overlap and use of heterospecific cues - Cassaing, Jacques; de la Riviere, Bettina; De Donno, Fabrice; Martinez-Garcia, Esteban; Thomas, Camille (ECOSCIENCE, 2013)
Familiarity with its habitat is vital for any individual, enabling it to meet its requirements for food, shelter, and reproduction. The questions of how optimal habitat is found and is shared with a competitor species remain problematic for rodents. Study of the habitat preferences and selection of 2 murinae from the south of France, the short-tailed mouse Mus spretus and the wood mouse Apodemus sylvaticus, found a large overlap in habitat and only small differences in preferences. Although both species live in almost every garrigue habitat and are more abundant in transitory human-disturbed areas, A. sylvaticus was higher in abundance in holm oak coppices, while M. spretus was more abundant in low scrubland with shrub oaks or thorny broom thickets. The high level of habitat overlap resulted in many co-occurrences, with A. sylvaticus always more abundant than the short-tailed mouse. When wood mice were experimentally introduced as an attractor in a low-suitability habitat, they surprisingly attracted many short-tailed mice, but fewer wood mice than were attracted by bait-only traps. Encounters arranged in situ between the attractor and the attracted mice showed predominantly amicable or neutral behaviours and very few instances of agonistic behaviour. We hypothesize that the demographic dominance of wood mice and the abundance of resources during a large part of the year resulted in a non-competitive cohabitation, which may be beneficial to short-tailed mice using wood mice cues as ``public information{''} indicating resource abundance.
The following values have no corresponding Zotero field: pub-location: PAVILLON CHARLES-EUGENE MARCHAND, LOCAL 0166, ST FOY, QUEBEC G1K 7P4, CANADA publisher: UNIVERSITE LAVAL
Keywords: habitat overlap; habitat preference; heterospecific